2020
DOI: 10.1007/s11908-020-0711-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Virus Co-infection in Acute Respiratory Infections in Children

Abstract: Purpose of Review This investigation aims to understand the role and burden of viral co-infections for acute respiratory illnesses in children. Co-infection can be either viral-viral or viral-bacterial and with new technology there is more information on the role they play on the health of children.Recent Findings With the proliferation of multiplex PCR for rapid diagnosis of multiple viruses as well as innovations on identification of bacterial infections, research has been attempting to discover how these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 97 publications
4
67
1
6
Order By: Relevance
“…We showed that RV replication is inhibited by prior infection with RSV-A and H1N1, while RV does not inhibit subsequent infection by these viruses. A number of clinical studies have described viral coinfections, particularly between RV, Flu, and RSV, but the clinical impact remains unclear 22 . Some publications have reported an enhancement in disease severity, while others have suggested the opposite 3,7,8,[23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…We showed that RV replication is inhibited by prior infection with RSV-A and H1N1, while RV does not inhibit subsequent infection by these viruses. A number of clinical studies have described viral coinfections, particularly between RV, Flu, and RSV, but the clinical impact remains unclear 22 . Some publications have reported an enhancement in disease severity, while others have suggested the opposite 3,7,8,[23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…The statistical package SPSS version 25.0 was used to analyze the data (SPSS Inc., Chicago, IL, USA). Categorical variables were compared using Pearson's chi-square test to compare patient characteristics, frequency of pathogen, and antibiotic use.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In critically ill patients with the Middle East respiratory syndrome (MERS), 18% had bacterial coinfections [ 23 ]. Viral-bacterial coinfections in the respiratory tract increase mortality and morbidity in children and adults [ [24] , [25] , [26] ]. As mentioned in a previous study, nearly 100% of COVID patients who died in the ICU had sepsis [ 4 ] The death of the non-survivors who tended to suffer from severe coinfection may be due to the need for invasive treatments such as tracheal intubation, tracheotomy or urinary tract intubation-assisted treatment.…”
Section: Discussionmentioning
confidence: 99%